Safety Engineering, Securitology and Insolvency - Vladimir Klaban (Communications, 2008)
The basis of safety engineering is acceptance, introduction and maintenance of measures aimed at safety in various, mainly technical areas of human activities. Safety is a state during which there is an admissible probability of occurrence of damage to protected interests. Insolvency is a state of incapacity to pay. In the contribution, the specified definitions are developed, their mutual relations are shown and their connection with sustainable development theory and practice is emphasised.